Effects of Gas/Oil Ratio (GOR), Lift Gas Injection rate and percentage choke opening on Casing-Heading Instability in a Gas-Lifted System - Adukwu, Ojonugwa (European Journal of Applied Sciences, 2022)
This research investigated the effects of gas/oil ratio, lift gas injection rate and percentage choke opening on casing-heading instability in gas lift system. The gas lift models and parameters used were first presented and injection valve flow rate at no oscillation was shown. The severity was monitored on the flow rate of gas through the injection valve. As the GOR decreases, chances of casing heading instability increases from damped oscillation to mild oscillation till severe oscillation takes place. On the other hand, increasing the flow of lift gas into the annulus reduces the chance of oscillation. The percent valve opening increase leads to increase in chances of instability. This knowledge helps in providing information needed to reduce or eliminate casing-heading instability. The study is important as casing heading instability leads to reduced average oil production which means the gas lift system is operated suboptimally.